THE IDEOLOGY OF LABOR LAW OF UKRAINE: WHAT IS IT NOW - Shcherbyna V.I. (Taras Shevchenko National University of Kyiv, 2024)
Ideology means the system of consolidated ideas and opinions formed into a certain integral theoretic concept that expresses ideological and value basics of the social organization, purposes and interests of its subjects, provides social activity programs, realizes into social life and lays to real guide to action.Labor law ideology – is the system of consolidating ideas and opinions which have been formalized into a certain entire theoretic concept (doctrine), that expresses ideological and value basis of social system, provides the opportunity for development of effective social activity algorithms of labour law subjects, realizes into social life, influences and lays to real guide to action through the labour norms.The central matter of the ideology of the labour law is forming of the doctrine of “production solidarity” – creation and normative fixation of the ideal model (construction) of social links between employees and employers within the framework of enterprises, institutions, organizations (production community) which is close to European standards and in which the national collectivist traditions have been realized and the general context of society knowledge has been taken into consideration. The main subject of this links is the production community.Speaking of normative fixation of the doctrine of “production solidarity”, the preconditions for possibility of building of complete system of norms and relations which they will regulate. Further we may talk of methods and means of influence on social relations. In particular, when it comes to idea of production solidarity, the core of the labour law norms which will regulate the relations of subjects within organization, use and protection of labour will be the willing of their subjects for common understanding, active communication and minimization of compulsion. Minutely such approach can be shown through such components of production solidarity idea as humanization and democratization of occupational environment, social justice guarantees in relations which create the object of labour law as well

Ідеологія – це система консолідуючих ідей та поглядів, які оформлені у певну цілісну теоретичну концепцію, що виражає ідейно-цінності основи суспільного устрою, інтереси та цілі її носіїв, передбачає програми соціальної діяльності, реалізується у суспільне життя та претендує на реальне керівництво до дії.Ідеологія трудового права – це система консолідуючих ідей та поглядів, які оформлені у певну цілісну теоретичну концепцію (доктрину), що виражає ідейно-цінності основи суспільного устрою, передбачає можливість розробки ефективних алгоритмів соціальної діяльності суб’єктів трудового права, реалізується у суспільне життя через дію норм трудового права та претендує на реальне керівництво до дії.Центральним питанням ідеології трудового права є формування доктрини «виробничої солідарності» – створення та нормативне закріплення ідеальної моделі (конструкції) суспільних зв’язків між працівниками і роботодавцями в рамках підприємства, установи, організації (виробничої громади), наближеної до європейських стандартів, і в якій реалізовано національні колективістські традиції та враховується загальний контекст суспільства знань. Головним суб’єктом цих зв’язків виступає виробнича громада.Якщо говорити про нормативне закріплення доктрини «виробничої солідарності», то з’являються передумови для можливості побудови цілісної системи ідей, норм і відносин, які вони будуть регулювати. Далі можна говорити і про способи та засоби впливу на суспільні відносини. Зокрема, якщо йдеться про ідею виробничої солідарності, то серцевиною норм трудового права, які регулюватимуть відносини суб’єктів із організації, застосування та захисту праці, буде бажання їх суб’єктів до порозуміння, активна комунікація та мінімізація примусу. Детально такий підхід може бути розкрито через такі ключові складові ідеї виробничої солідарності як гуманізація та демократизація виробничого середовища, а також гарантування соціальної справедливості у відносинах, які складають предмет трудового права.
ІДЕОЛОГІЯ ТРУДОВОГО ПРАВА УКРАЇНИ: ЩО ЦЕ НИНІ
Keywords: ideology; labor law ideology; doctrine of “production solidarity”; production community; humanization and democratization of occupational environment; social justice guarantees.; ідеологія; ідеологія трудового права; доктрина «виробничої солідарності»; виробнича громада; гуманізація та демократизація виробничого середовища; гарантування соціальної справедливості.